2015
DOI: 10.2147/ijn.s90733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver nanoparticles on neonatal testis development in mice

Abstract: Background Metal nanoparticles (MNPs) play an important role in consumer products. An increasing use of MNPs has raised concerns about potential risks for human health. Therefore, in vivo tests of MNPs are urgently required. Using mice as a model animal, the aim of the present study was designed to investigate the effect of biologically synthesized silver nanoparticles (AgNPs) on spermatogenesis in neonatal mice. Methods AgNPs were synthesized using Bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…There are some limited in vivo studies about the Ag NPs toxicity, it was shown that these NPs induced some harmful impacts on reproduction, malformations, and various morphological destructions in different animal models ( Zhang X.F. et al, 2015 ).…”
Section: Toxicity Of Common Metallic and Metal Oxide Npsmentioning
confidence: 99%
“…There are some limited in vivo studies about the Ag NPs toxicity, it was shown that these NPs induced some harmful impacts on reproduction, malformations, and various morphological destructions in different animal models ( Zhang X.F. et al, 2015 ).…”
Section: Toxicity Of Common Metallic and Metal Oxide Npsmentioning
confidence: 99%
“…Furthermore, ENPs can cross the blood-brain barrier (BBB) and promote the expression of proinflammatory cytokines, including IL-1 α , TNF- α and NF- κ B [ 10 ], which may increase the risks of neurodegenerative disease and brain cancer. ENPs can also cross BTB and alter the spermatogenesis process by inducing apoptosis or necrosis of spermatocytes and Sertoli cells as well as reducing sperm motility, quality and quantity [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Henceforth, the toxicity of AgNPs has been studied widely in many in vitro [4][5][6] and in vivo models [1,7,8]. Recent studies have demonstrated the adverse effects of AgNPs on the male reproductive tract, particularly spermatogenesis and the quality of sperm and male somatic cells and spermatogonial stem cells [9,10]. Early exposure to AgNPs has the potential to disrupt fetal and postnatal health in the embryo and abnormal development of the placenta [11].…”
Section: Introductionmentioning
confidence: 99%